The outcomes of surgical treatment of closed humeral shaft fractures in adults: Plates versus Nails - غانم, كميت; أحمد جوني ,; علي يوسف , (Latakia University Journal -Medical Sciences Series, 2022)
Purpose: To compare functional outcomes, union and complication rates in patients treated with locked intramedullary nailing or dynamic compression plating for humeral shaft fractures. Methods: 25 men and 14 women with humeral shaft fractures were randomised to undergo locked antegrade intramedullary nailing (IMN, n=22) or dynamic compression plating (DCP, n=17). Patients with pathological fractures, open fractures, neurovascular injury, or fractures for more than 2 weeks were excluded. Fractures were classified according to the AO classification system 25 were injured in road traffic accidents. The functional outcome (according to the American Shoulder and Elbow Surgeons [ASES] score) and rates of union and complication of the 2 groups were compared. Results: All patients were followed up for a minimum of 12 months. In the respective IMN and DCP groups, Locked intramedullary nailing versus dynamic compression plating for humeral shaft fractures the mean ASES scores were 91.5 and 91.3 (p=0.89), , the non-union rates were 4.5% and 0% (p=0.3). In the DCP group 2 had transient radial nerve palsies , one superficial infection, in IMN group 4 had shoulder impingement , one underwent re-operation for implant failure. Conclusion: functional outcomes were good in both methods , and the surgery time was shorter in IMN group.